La métamorphose de Yurupari : flûtes, trompes et reproduction rituelle dans le Nord-Ouest amazonien - Dimitri Karadimas (Journal de la Société des Américanistes)
The metamorphosis of Yurupari : flutes, trumpets and ritual reproduction in the Northwest Amazon. In this article, the author proposes to analyse different mythological figures known in the North-West Amazon as Yurupari. Making a comparison between some ethnographical data from the Miraña, from the Tukano speaking groups of the Vaupes and from the Arawak groups north of the area, it appears that a solitary wasp is the common element of these mythological figures. This wasp reproduces itself using their preys as a receptacle and as food for its offspring. When anthropomorphized by the North-West Amazon populations, this pseudo-parasitical behaviour is seen as an insemination. Along with other characteristics and components from the hymenopter, this behaviour is an essential referent as much for the male initiation ritual as for the prohibition to see the sacred flutes that exists for women, thus constructing ideologically the bodies of both sexes. The contribution will explore the major mythological and ideological implications of this identification.